G321(P) Fix freddie!. (27th April 2015) - Cleugh, F; Langseth, A; Clements, C; Salam, M
Abstract : Background: Facing higher than average unscheduled care use in a busy inner city paediatric unit, with a significant proportion of low acuity conditions, a need to become proactive in tackling the pressure was recognised. Collaborated as part of new innovative integrated paediatric care model with puppet company to produce Fix Freddie! Pilot tour Spring 2014. Objectives: Better understanding of how local community accesses children's unscheduled care bringing together communities and professionals across the whole system, to support families in feeling confident to navigate system and care for their children's health needs reduce pressures on the local emergency and urgent care system Methods: Explored different settings and workshop styles (Table 1 ). Parents/carers asked to complete a pre show questionnaire. After the show, explored issues with: small parent focus groups classroom-based discussion and picture drawing fete style event with informal conversations with professionals Feedback obtained with Post-It comments on "Freddie Feedback" poster. Information leaflet distributed with advice about where to seek advice, self management, and information about local services. Filmed to capture impact of events on children, parents and professionals. Results: Pre show questionnaire Completed by 46 parents of 85 children. 53% white british; 47% diverse ethnic mix. Chart A how seek child health advice – 85% GP, 21% ED, 42% family and friends, 37% internet. Chart B services use when worried – 89% GP, 52% ED Parents most consistently worried by fever, 52% would seek GP review 41% would go to A&E. Other concerns included cough, vomiting, diarrhoea, abdominal pain. Attended ED and the GP with similar illnesses. 26% reported issues in accessing care, primarily lack of same day GP appointments. Key themes surfaced from Fix Freddie! Feedback (Table 2 ) Better understanding of local services available, notably about 111 Improved knowledge and confidence about self managing minor illnesses and injuries Additional awareness raised about safety at home General positive feedback for puppet show and events Conclusion: Fix Freddie! has provided a fun and engaging way to make new connexions across the whole system, facilitating co-design of local solutions to problems of healthcare accessibility and confidence in self management. Local CCG commissioners are now funding a wider local tour and we are working on next steps to broaden reach of the events.